063 Assessing treatment burden in chronic heart failure patients. (22nd September 2015) - Gallacher, KI; May, C; Montori, VM; Mair, FS
Abstract : Introduction: Non-adherence is a well recognised avoidable precipitant of emergency admissions in chronic heart failure (CHF) patients. CHF patients often have multiple co-morbidities, each with complicated management plans. "Treatment burden" is the "work" undertaken by patients managing a chronic condition, and includes understanding treatments, engaging with others, taking complicated medication regimes, enacting lifestyle advice and attending hospital appointments. Our aim is develop an understanding of treatment burden in CHF patients, enabling us to identify points and types of intervention that would reduce non-adherence and potentially improve outcomes. Methods: Secondary qualitative analysis of 46 interviews with CHF patients: 30 male; 20 female; aged between 45 and 88 years (mean age 73 yrs). Using normalisation process theory (NPT) as a coding framework, the data were categorised into the four NPT domains: coherence; cognitive participation; collective action; reflexive monitoring. Each of these domains has four subcategories as shown in Abstract 63 Table 1 . Two researchers analysed all the transcripts and discussed any disagreements. Any dispute was resolved by a third party. Any data that fell outside of the NPT were noted. A taxonomy of "treatment" work was then created. There are four domains – Coherence, Cognitive Participation, Collective Action, Reflexive Monitoring. Each has four subcategories. Abbreviations are used to identify each subcategory e.g. for the domain "Coherence (CO)", subcategory "Differentiation (DI)" is written "CODI". Results: Workload or burden of treatment was described by patients across all four domains. Very little data fell outside the NPT framework, and any that did was emotional work which is not included in NPT. Abstract 63 Figure 1 shows the frequency of different types of burden, with the scale reflecting the number of times a category was recorded (see Abstract 63 Table 1 for key of categories). The most frequent category of work mentioned was enacting work such as taking multiple medications or attending multiple hospital appointments, the least mentioned was keeping up to date with current treatments. A taxonomy of treatment burden was constructed. Conclusion and Implications: We have created a conceptual model of treatment burden in CHF patients which can be used to inform the development of a scale to measure treatment burden.